Effect of partial rootzone drying on the concentration of zeatin-type cytokinins in tomato (Solanum lycopersicum L.) xylem sap and leaves - Kudoyarova, Guzel R (Journal of experimental botany, 2007)
Decreased cytokinin (CK) export from roots in drying soil might provide a root-to-shoot signal impacting on shoot physiology. Although several studies show that soil drying decreases the CK concentration of xylem sap collected from the roots, it is not known whether this alters xylem CK concentration ([CK(xyl)]) in the leaves and bulk leaf CK concentration. Tomato (Solanum lycopersicum L.) plants were grown with roots split between two soil columns. During experiments, water was applied to both columns (well-watered; WW) or one (partial rootzone drying; PRD) column. Irrigation of WW plants aimed to replace transpirational losses every day, while PRD plants received half this amount. Xylem sap was collected by pressurizing detached leaves using a Scholander pressure chamber, and zeatin-type CKs were immunoassayed using specific antibodies raised against zeatin riboside after separating their different forms (free zeatin, its riboside, and nucleotide) by thin-layer chromatography. PRD decreased the whole plant transpiration rate by 22% and leaf water potential by 0.08 MPa, and increased xylem abscisic acid (ABA) concentration 2.5-fold. Although PRD caused no detectable change in [CK(xyl)], it decreased the CK concentration of fully expanded leaves by 46%. That [CK(xyl)] was maintained and not increased while transpiration decreased suggests that loading of CK into the xylem was also decreased as the soil dried. That leaf CK concentration did not decline proportionally with CK delivery suggests that other mechanisms such as CK metabolism influence leaf CK status of PRD plants. The causes and consequences of decreased shoot CK status are discussed